AERODYNAMIC ANALYSIS OF WIND DEFLECTOR DESIGN ON PICK UP BOX CARS BASED ON CFD - Imam Krismunandar; Oktarina Heriyani (Magister Teknik Mesin Universitas Pancasila, 2026)
This study aims to analyze the effect of adding a wind deflector on the aerodynamic performance of a pick-up box truck using the Computational Fluid Dynamics (CFD) method. The primary issue with this type of vehicle is the significant pressure drag caused by the height difference between the cabin and the cargo box. Simulations were conducted using ANSYS Fluent software with the k-epsilon turbulence model on two configurations: a standard model and a model equipped with a wind deflector. The simulation results show that the standard model experiences significant flow separation in the gap between the cabin and the box, resulting in a drag coefficient (C_d) of 0.5239 and a drag force (F_d) of 2.904 N. Following the application of the wind deflector, the airflow becomes more streamlined and the separation point is minimized, reducing the C_d value to 0.4240 and F_d to 2.347 N. This study concludes that the use of a wind deflector can provide a drag force reduction of 19.19%, indicating a significant improvement in the vehicle's aerodynamic efficiency.